Desenvolvimento de modelos físicos reduzidos para avaliação de fundações por estacas helicoidais em solos reforçados com geossintéticos - Chaves, Charles Pereira (2016)
Soil reinforcement with helical piles is still a subject that has been under development over the past decades. In this research, a shallow condition helical anchor prototype is proposed. It was built in a sandy soil reinforced with a geogrid. A metal rigid box was used to construct the prototype. The main objective of this study is to evaluate the influence of geosynthetic reinforcement on the anchoring system. In this regard, an experimental loading test program was performed in two groups: unreinforced soil tests an geogrid-reinforced soil ones. Four tests were conducted with anchors installed in unreinforced sand in order to standardize a test methodology, which assures repeatability on the same geotechnical conditions, and to define the pullout resistance in such condition. Three tests were performed with helical anchors installed in geogrid-reinforced sand. In the first geogrid-reinforced test, a single geosynthetic layer was placed over the sand soil, immediately above the upper helix. The two last tests in reinforced condition were performed with the geogrid placed on the same position, but folder upright in order to increase the soil-geosynthetic interaction. It was not observed any significant difference in the beginning of the load-displacement curve between tests performed under unreinforced and reinforced conditions. On the other hand, anchors pullout resistance in geogrid-reinforced sand has notably increased at larger displacements. This aspect has minor importance since practical displacements were already reached. Tests performed under unreinforced condition were also used to determine the actual slope of the rupture surface of the prototype, by mapping the soil surface displacements before and after the tests. It was compared with suggestions found in the technical literature. The geogrid-reinforcement was effective to improve helical anchor behavior only under high displacement values, usually above the allowable displacement of the anchor.